Aconselhamento pastoral on-line com adolescentes - Streck, Valburga Schmiedt (2012)
The article describes the use of the Internet by adolescents and the meaning of pastoral care. The Internet is presented as a living environment, where children and adolescents may find meaning, stability and orientation. The focus is not put on forms of pastoral care in the traditional settings like pastoral care by telephone. It is centered around ways of self-organization of adolescents and the development of resilience as a possibility of survival in an ever increasingly chaotic world.